Enabling white, Afrikaans-speaking adolescents towards post-divorce resilience: implications for educators - Linda Theron; Nadine Dunn (South African Journal of Education, 2010)
Using rich qualitative data, we describe the ecosystemically-embedded protective antecedents that enabled 10 white, Afrikaans-speaking adolescents from divorced families towards resilience. The description both confirms and extends what was known about the roots of adolescent resilience, post-divorce. We use these findings to capacitate educators who are mandated to care for needy learners, such as those from divorced homes. The findings provide more than mere implications for educators - given their simplicity, they make it possible for educators to make the most of these to champion resilience.